WATER DROPLET MOTION UNDER THE INFLUENCE OF SURFACE ACOUSTIC WAVES (SAW) - Insepov, Zinetula; Ramazanova, Zamart; Zhakiyev, Nurkhat; Tynyshtykbayev, Kurbangali (Journal of Physics Communications, 2021)
The water droplet motion processes actuated by applying surface acoustic waves at various RF powers and frequencies were investigated by numerically modelling and compared with experiment. A three-dimensional computational model of a free water droplet streaming on the surface of the substrate have been developed using Finite Element Method (FEM) with Laminar Two-Phase Flow Moving Mesh approach for Navier–Stokes equations which were coupled with Convection Wave equation (CWE) module of the COMSOL Multiphysics...
Keywords: water actuation; streaming; droplet motion; SAW device; Surface Acoustic Waves